Growth Evaluation of Selfcrossed Progenies BC1F2 Experiencing Submerged and Non-submerged at BC1F1 and its Parents - Maulidya, Azzah; Agus Suwignyo, Rujito; Susilawati; Muhardiyanto, Cahya (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2024)
Abstract: A non-tidal swamp can increase rice cultivation and production, but its use is still dependent on natural conditions, making plants vulnerable to submergence and drought stress. Developing dual-tolerant varieties is essential for rice cultivation in non-tidal swamps. Inpara 8 carries the SUB1 gene, providing tolerance to submergence stress, while Inpago 5 is tolerant to drought stress. This study aimed to evaluate the growth of BC1F2 progeny from a cross between Inpara 8 and Inpago 5 under submerged stress, along with their parents (Inpago 5 and Inpara 8). The research was conducted in the greenhouse of the Agriculture Faculty at Sriwijaya University at coordinates 3°13'11.1